STRATEGI REWARD DAN PUNISHMENT DALAM MENINGKATKAN MOTIVASI BELAJAR BAHASA ARAB DI MTs AL-QODIR MENEMENG - Nadia Ainun Nufus; Abdul Aziz (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of reward and punishment strategies in enhancing students' motivation to learn Arabic at MTs Al-Qodir Menemeng. This study employed a qualitative approach with a phenomenological design to explore in-depth experiences and perceptions of teachers and students regarding the execution of these strategies. Data collection techniques included observation of learning activities, semi-structured interviews with Arabic teachers and students, and documentation related to learning programs and school policies. The data were analyzed using thematic analysis to identify main patterns and themes associated with changes in students' learning motivation and behavior. The results indicate that the provision of rewards in the form of verbal praise, symbolic academic recognition, and simple material prizes based on academic achievement contributes positively to increased student participation, discipline, and self-confidence in Arabic learning. Meanwhile, educational and proportional punishments, such as additional academic assignments and parental involvement for severe violations, proved effective in curbing negative behavior without causing detrimental psychological impacts on students. These practices align with the principles of positive reinforcement and logical consequences in behavioristic theory, as well as the concepts of ta’dib and targhib wa al-tarhib in Islamic education. However, this study also found that students' learning motivation remains dominated by reward-oriented goals, resulting in intrinsic motivation and the appreciation of Arabic as a communicative skill not yet being optimally developed.